Workplace Incentives and Organizational Learning - Francesco Amodio; Miguel A. Martinez-Carrasco (Institute of Labor Economics (IZA), 2020)
This paper studies learning within organizations when incentives change. We use a simple principal-agent model to show how, in the presence of imperfect information over the shape of the production function, worker's effort choice changes over time as information is disclosed and processed. We also show that changes in workers compensation can trigger such learning process. We test this hypothesis using personnel records from a Peruvian egg production plant. Exploiting a sudden change in the compensation schedule, we find that workers learn from each other over the shape of the production function. This adjustment process is costly for the firm.
Keywords: D22; D24; J24; J33; M11; M52; M54; O12; 330; organizational learning; workplace incentives; inputs